Comprometimento do estudante: um elo entre aprendizagem e inclusão social na qualidade da educação superior - Felicetti, Vera Lucia (2011)
The higher education has been increasingly responsible for scientific, technological and social development of a nation. So, in addition to the efforts of all involved in this educational context, the educational policies are also relevant in improving the quality of education at this level of learning. This dissertation is inserted into the Joint Research Program CAPES / UTexas: Quality in Education, under announcement: CGCI No. 024/2007. It aims to examine the engagement of the scholarship awarded students from the University for All Program PROUNI (started in 2005) with their learning and the impacts that these new graduates may trigger in both university and society. The issue of quality in higher education is approached from the dimensions established by Harvey (2004-2011) and Entwistle (2005): input, process, and outcome. The dimensions shown are in line with the research problem of this dissertation: Is the PROUNI students‟ engagement with their learning related with success in their academic training? Does the PROUNI graduate causes impact in both university and society? The theoretical approach provides a look at the issue of quality in higher education; brings the historical construction of engagement ; addresses pedagogical and learning style theories; presents the historical evolution of the access to higher education in Brazil, highlighting the PROUNI and its organization; addresses the question of the impact on the bias of the social responsibility of Higher Education Institution and the issue of employability and satisfaction of this new graduates‟ profile. The methodological approach used in this dissertation has both quantitative and qualitative focuses, with explanatory objective and ex post facto technical procedure. The research involved PROUNI students from a nonprofit university in the state of Rio Grande do Sul who started the program in 2005, (492), those who graduated by 2010 (198) and those who answered the proposed survey instrument (134). The results of this study were associated to the dimensions directed to the quality in higher education. The input dimension was contemplated by all PROUNI students, characterized by their initial conditions upon entering academic life. In the process dimension, it was identified that arising difficulties in the academic pathway were overcome up by engagement. Indicators of engagement correlated with indicators of impact on society, and the Higher Education Institution. In this process, it was also identified correlations between indicators of learning styles related to sociological and physiological stimuli. In the outcome dimension were identified potential impacts generated by the new profile of graduates at both university and society, such as the relationship between employment and work, satisfaction and the influences and/or incentives that these graduates trigger in society. This way, it has been proved that the real or potential outcomes in the training of the PROUNI graduate are related to student‟s engagement with his or her learning.